U.l.S. 3D domain of rectangular cross-sections in r.c. subject to shear and torsion. (15th November 2016) - Beninato, Francesco; Foti, Dora; Vacca, Vitantonio
Graphical abstract: The formulas and procedures utilized for the plane domains are applied to the spatial domain. The approach is more uniform, synthetic and comprehensive respect to the current approaches on the use of separate domains. Highlights: Innovative unitary approach to the U.L.S. design and check of r.c. sections subject to the composed shear-torsion stress. Determination of the angle θ of the concrete compressive connecting rods. A 3D strength domain ( acting shear-acting torsion-θ ) is proposed to determine the shear and torsional strengths of the section. The approach is in line with the current codes – Italian D.M. 2008 and its Circular n. 617 (2009), EC2, etc. Shear-torsion curves depending on the acting stresses and/or the eccentricity. Abstract: This paper aims to illustrate a unified approach for the process of the Ultimate Limit State (ULS) design and check of rectangular sections in reinforced concrete (r.c.) subject to composed forces of shear and torsion. This approach was developed by the authors starting from established theoretical hypotheses and categorizations and from the resulting equations; it can solve the shear-torsion problem in a unified and organic way considering a single 3D resistance domain obtained from assembling three distinct 2D graphics actually utilized in the current procedure. The 3D domain has the high advantage to propose a more comprehensive approach to the problem and more careful and precise results.